Missed opportunity for self-injectable contraception awareness and adoption: Insights from client exit interviews in Uganda and Nigeria - Susan Ontiri; Claire Rothschild; Doreen Nakimuli; Oluwatosin Adeoye (Elsevier, 2023)
Objectives: To assess the extent to which self-injection contraceptive information and services are provided to women in Uganda and Nigeria. Study design: We conducted a descriptive information cascade analysis using data from a cross-sectional exit interviews with 492 family planning clients in Uganda and 720 in Nigeria. Results: More than a third of respondents in Uganda (31.2%) and Nigeria (40.5%) reported not receiving any information about the self-injection contraceptive during service provision. Only 45.6% clients who adopted self-injected DMPA-SC in Uganda and 1.7% in Nigeria were issued with additional doses to take home. Conclusion: The findings suggest that there are missed opportunities to provide women with information and services on DMPA-SC self-injection. Implication: A contraceptive counseling and services cascade can be a useful tool for identifying gaps in the quality and person-centeredness of family planning services, and ultimately improving the experience of clients.